2009
DOI: 10.1016/j.obhdp.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Why don’t well-educated adults understand accumulation? A challenge to researchers, educators, and citizens

Abstract: a b s t r a c tAccumulation is a fundamental process in dynamic systems: inventory accumulates production less shipments; the national debt accumulates the federal deficit. Effective decision making in such systems requires an understanding of the relationship between stocks and the flows that alter them. However, highly educated people are often unable to infer the behavior of simple stock-flow systems. In a series of experiments we demonstrate that poor understanding of accumulation, termed stock-flow failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
461
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 279 publications
(488 citation statements)
references
References 46 publications
(58 reference statements)
25
461
2
Order By: Relevance
“…As research in risk perception, cognitive psychology, and people's values and beliefs suggests, this "cultural" lens colors our general beliefs about society and the environment (51,59). In addition, certain heuristics, mental shortcuts, lead to the tendency to underestimate risks arising from climate change (60)(61)(62)(63). Cognitive filters shape our perceptions, constrain our attitudes about options (and others involved in the process), and influence our decision-making processes (11,38).…”
Section: Contextmentioning
confidence: 99%
“…As research in risk perception, cognitive psychology, and people's values and beliefs suggests, this "cultural" lens colors our general beliefs about society and the environment (51,59). In addition, certain heuristics, mental shortcuts, lead to the tendency to underestimate risks arising from climate change (60)(61)(62)(63). Cognitive filters shape our perceptions, constrain our attitudes about options (and others involved in the process), and influence our decision-making processes (11,38).…”
Section: Contextmentioning
confidence: 99%
“…The majority in these and subsequent experiments fail to apply the basic principles of accumulation. Rather, people often use the intuitively appealing "correlation heuristic" (Cronin et al 2009 ) , assuming that the output of a system should "look like"-be positively correlated with-its inputs. Although sometimes useful, correlational reasoning fails in systems with important accumulations.…”
Section: S S T S I O T S I O Tmentioning
confidence: 99%
“…This research improves our understanding of the Stock-Flow (SF) Failure, found to be a robust problem in the perception of accumulation (Cronin, Gonzalez, & Sterman, 2009). We demonstrate the SF Failure with an interactive simulation in a relevant climate change context (Dynamic Climate Change Simulator (DCCS).…”
mentioning
confidence: 83%
“…Growing evidence indicate human misunderstanding of the basic building blocks of dynamic systems, including stocks, inflows and outflows (Booth Sweeney & Sterman, 2000;Cronin & Gonzalez, 2007;Cronin, Gonzalez, & Sterman, 2009;Sterman & Booth Sweeney, 2002). Many people, often highly educated in mathematics and sciences, fail to understand a basic principle of dynamic systems: that a stock rises (or falls) when the inflow exceeds (or is less than) the outflow (Cronin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%